The Effects of Boiling and Steaming on The Yield and Nutrient Content of Fish Meal - Nur Aini, Fitria; Latief, M. Fadhlirrahman; Wahyu, Windari (Jurnal Nutrisi Ternak Tropis, 2024)
This study aimed to evaluate the effects of boiling and steaming processes on yield and nutrient content in fishmeal production. Fish samples, including Mackerel Scad and Sardinella lemuru were obtained from Sendang Biru, Malang and processed using boiling and steaming methods at 90-100?C for 30 minutes. This study used 4 treatments i.e boiled mackerel scad, steamed mackerel scad, boiled Sardinella lemuru and steamed Sardinella lemuru. The results indicated that steaming yielded a higher yield compared to boiling (8.56 and 1.54%), but the nutrient content particularly ash, protein and ether extract was different in both of fishmeal. However, steaming is more effective in lowering crude fiber levels than boiling. The study also assessed Salmonella contamination in fishmeal, and the analysis revealed no Salmonella contamination in the steaming fishmeal samples. These findings provide valuable guidance for the livestock feed industry in selecting the optimal processing method to maximize the quality of fishmeal.